Issues and Solutions of Legal Protection for Marine Mammals in Indonesia - Anggita, Leli; Nugraha, Adrian (Universitas Muhammadiyah Purwokerto, 2025)
The government has tried to protect marine mammals through Marine Protected Areas (MPA) contained in laws and regulations. However, the lack of conservation areas specifically designed for marine mammals and several counterproductive laws have created problems in efforts to protect marine mammals. This research was carried out using normative legal research methods through literature studies that examined mainly secondary data. Several issues related to the extinction of marine mammals arise due to the lack of protected areas specifically designed for marine mammals, overlapping management institutions, and centralization of power, which makes efforts to manage marine areas complex and challenging to recognize the existence of indigenous peoples. The government can implement several solutions related to this problem, including expanding the conservation areas specifically designed for marine mammals, clarifying and synchronizing any regulations governing institutional authority, and recognizing the existence of indigenous peoples and their traditions.